Variable ecological conditions promote male helping by changing banded mongoose group composition. (26th January 2016) - Marshall, Harry H.; Sanderson, Jennifer L.; Mwanghuya, Francis; Businge, Robert; Kyabulima, Solomon; Hares, Michelle C.; Inzani, Emma; Kalema-Zikusoka, Gladys; Mwesige, Kenneth; Thompson, Faye J.; Vitikainen, Emma I. K.; Cant, Michael A.
Lay Summary: Male banded mongooses babysit more when rainfall is variable. Banded mongooses live in cooperative family groups and males in particular help raise pups that are not necessarily their own. It has been suggested that ecological conditions affect cooperation, and our study confirms that the variability of conditions is important: Females face higher mortality during years with more variable rainfall, and males may be better off helping their relatives when there are fewer opportunities for mating. Twitter: @HarryHMarshall Abstract: Ecological conditions are expected to have an important influence on individuals' investment in cooperative care. However, the nature of their effects is unclear: both favorable and unfavorable conditions have been found to promote helping behavior. Recent studies provide a possible explanation for these conflicting results by suggesting that increased ecological variability, rather than changes in mean conditions, promote cooperative care. However, no study has tested whether increased ecological variability promotes individual-level helping behavior or the mechanisms involved. We test this hypothesis in a long-term study population of the cooperatively breeding banded mongoose, Mungos mungo, using 14 years of behavioral and meteorological data to explore how the mean and variability of ecological conditions influence individual behavior, body condition, and survival. Female body condition was more sensitive to changes in rainfall leading to poorer female survival and pronounced male-biased group compositions after periods of high rainfall variability. After such periods, older males invested more in helping behavior, potentially because they had fewer mating opportunities. These results provide the first empirical evidence for increased individual helping effort in more variable ecological conditions and suggest this arises because of individual differences in the effect of ecological conditions on body condition and survival, and the knock-on effect on social group composition. Individual differences in sensitivity to environmental variability, and the impacts this has on the internal structure and composition of animal groups, can exert a strong influence on the evolution and maintenance of social behaviors, such as cooperative care.